2022
DOI: 10.7150/ijbs.70567
|View full text |Cite
|
Sign up to set email alerts
|

Alizarin, a nature compound, inhibits the growth of pancreatic cancer cells by abrogating NF-κB activation

Abstract: The current performance of nature compounds in antitumor field is gradually attracted more and more attention, we discovered a nature active ingredient alizarin possess potent natural reductive NF-κB activity to against pancreatic cancer. However, the preclinical pharmacology and therapeutic effect, and the underlying mechanisms of alizarin in inhibiting pancreatic cancer are still unclear. After high-throughput screening, this is the first report that alizarin can induce a potent inhibitory effect against pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…13 Alizarin exhibited a potent antipancreatic cancer capability by abrogating activation of nuclear factor kappa B (NF-κB) . 14 Moreover, alizarin inhibits insulin-induced fibrillation and amyloid-induced cytotoxicity. 15 On the basis of these, it was demonstrated that alizarin has several biological effects including antibacterial, antitumor, antioxidation, and anti-Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…13 Alizarin exhibited a potent antipancreatic cancer capability by abrogating activation of nuclear factor kappa B (NF-κB) . 14 Moreover, alizarin inhibits insulin-induced fibrillation and amyloid-induced cytotoxicity. 15 On the basis of these, it was demonstrated that alizarin has several biological effects including antibacterial, antitumor, antioxidation, and anti-Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Alizarin is a synthetic anthraquinone found in the roots of the madder plant. Its IC 50 for growth inhibition in a range of pancreatic cancer cells is approximately 12 µM (Xu et al, 2022), which is an order of magnitude greater than its NAT1 inhibitory concentration. This compound warrants further investigation both in vitro and in vivo as a possible selective NAT1 inhibitor.…”
Section: A Pharmacological Inhibitors Of Arylamine N-acetyltransferas...mentioning
confidence: 86%
“…Alizarin is an orange crystal or ochre yellow powder with the chemical name 1,2-dihydroxyanthraquinone. It has anticoagulants [ 58 ] and anti-cancer activities [ 89 ].…”
Section: Chemical Classification Of Natural Pigmentsmentioning
confidence: 99%